Environmental pollution and the fetus - Kadriye Yurdakök (Hygeia Press di Corridori Marinella, 2012)
A child is a growing and developing human being early from conception throughout the end of adolescent period. Children at any stages of growth and development need to be protected from environmental health hazards. They need safe and health promoting environment to reach their optimum growth and development that they are capable genetically. However physical, chemical, biological and social environments have changed throughout decades and children of today are living in a very different environment than from their grandparents and parents. Today they are at most risk of being exposed to new chemicals that are mostly not tested for fetus and children. Since World War II, approximately 80,000 new synthetic chemicals have been manufactured and released into the environment in large amounts, with 10 new chemicals being introduced every day. The vast majority of these chemicals have not been studied adequately for their impacts on human health or their particular impacts on fetus. Many of these synthetic chemicals are persistent and bio-accumulative, remaining in the human body long after the exposure. Parental exposures occurred before the conception threatens the fetus both because the maternal or paternal reproductive organs are affected and because chemicals that can be accumulated in the mother's body before pregnancy may be mobilized and cross over placental barrier during pregnancy. Many synthetic chemicals are already present in cord blood and we do not know how these multi-chemical exposures affect programmed development of fetus and studies are limited on long term effects of single chemical exposure. Some examples of health effects resulting from developmental exposures include those observed prenatally and at birth such as miscarriage, stillbirth, low birth weight, birth defects. Establishing a causal links between specific environmental exposures and complex multifactorial health outcomes is difficult and challenging.